2018
DOI: 10.1002/ejoc.201801532
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium‐Catalyzed C–H Selenylations of Benzamides

Abstract: A convenient and effective protocol for the ruthenium‐catalyzed C–H selenylations of benzamide was achieved under mild reaction conditions. The robust ruthenium catalyst tolerated a wide range of functional groups and set the stage for the preparation for diversely decorated benzamides. The amide directing group could be transferred to carboxylic acid, aldehyde and tetrazoles. Preliminary mechanistic study indicated a base‐assisted electrophilic‐type substitution C–H activation event.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 92 publications
(25 reference statements)
0
15
0
Order By: Relevance
“…The more steric hindrance 2-aryl acetamides and electron-efficient diselenide substrates also remains a challenge. In continuation of our work [14] and those of others on the catalytic synthesis of unsymmetrical diaryl selenides, herein, we disclose the efficient palladium (II)-catalyzed ortho-selenylations of synthetically useful aryl acetic amide with…”
Section: Full Papermentioning
confidence: 70%
“…The more steric hindrance 2-aryl acetamides and electron-efficient diselenide substrates also remains a challenge. In continuation of our work [14] and those of others on the catalytic synthesis of unsymmetrical diaryl selenides, herein, we disclose the efficient palladium (II)-catalyzed ortho-selenylations of synthetically useful aryl acetic amide with…”
Section: Full Papermentioning
confidence: 70%
“…N-cyclohexyl-2-(phenylselanyl)benzamide 12b Yield: 60%; mp 183–185 °C (lit. [ 22 ] mp 179–181 °C); 1 H NMR (400 MHz, CDCl 3 ) δ = 1.21–1.31 (m, 3H), 1.40–1.50 (m, 2H, CH 2 ), 1.65–1.69 (m, 1H), 1.74–1.80 (m, 2H, CH 2 ), 2.05–2.09 (m, 2H, CH 2 ), 3.97–4.07 (m, 1H, N-CH), 5.32 (bs, 1H, NH), 7.09–7.11 (m, 1H ar ), 7.17–7.23 (m, 2H ar ), 7.35–7.41 (m, 3H ar ), 7.50–7.54 (m, 1H ar ), 7.60–7.65 (m, 2H ar ); 13 C NMR (100.6 MHz, CDCl 3 ) δ = 24.83 (2 × CH 2 ), 25.55 (CH 2 ), 33.07 (2 × CH 2 ), 48.87 (CH), 125.76 (CH ar ), 127.33 (CH ar ), 128.42 (CH ar ), 129.55 (2 × CH ar ), 130.01 (C ar ), 130.80 (CH ar ), 131.26 (CH ar ), 134.60 (C ar ), 135.04 (C ar ), 135.88 (2 × CH ar ), 167.38 (C=O); 77 Se NMR (76 MHz, CDCl 3 ) δ = 434.17 ppm; IR: 3251, 3053, 2924, 2849, 1618, 1583, 1541, 1459, 1448, 1436, 1377, 1337, 1299, 1283, 1256, 1240, 1191, 1149, 1120, 1081, 1066, 1030, 1018 cm −1 ; Elemental Anal. Calcd for C 19 H 21 NOSe (359.08): C, 63.68; H, 5.91; N, 3.91 Found: C, 63.52; H, 5.86; N, 3.83.…”
Section: Methodsmentioning
confidence: 99%
“…Ackermann, Ma, and co-workers reported a ruthenium-catalyzed CÀ H selenylation of benzamides providing the monoselenylated products in good to excellent yields. [31] In addition to selective mono-selenylated products which were obtained in good yields via CÀ H metal-catalyzed activation, the authors demonstrated that the directing group can be removed under mild reaction conditions, affording compounds that can be applied in medicinal chemistry. Recently, Nakamura, Shang, and co-workers described a procedure for chromium-catalyzed C(sp 2 )À H functionalization of ortho-position of secondary amides in the presence of trimethylaluminum as a base, for the selective formation of alkynylated products.…”
Section: Monodentate N-based Groupsmentioning
confidence: 99%